Enhancing Students’ Speaking Abilities through Paired Storytelling Strategies - Arnita Annisa Belly; Sukarno Sukarno; Dwiyani Pratiwi (Jurnal Pendidikan Progresif, 2024)
Enhancing Students' Speaking Abilities through Paired Storytelling Strategies. This study examined how using storytelling as a teaching strategy affected students' ability to communicate more clearly. The participants included thirty students from SMP Muhammadiyah 3 Yogyakarta, chosen through purposive sampling and split into experimental and control groups. The experimental group received storytelling instruction over four consecutive sessions, while the control group did not. Both groups were assessed on their speaking skills before and after the intervention. Results showed that the experimental group's post-test mean score was 96.0, compared to a pre-test mean score of 72.0. Specifically, the control group's mean post-test score was 64.0, an increase from the pre-test score of 60.0. The oral proficiency scores from each indicator demonstrated that students in the experimental group improved after being taught using paired storytelling, while the control group's scores did not improve. A one-group t-test demonstrated that post-test scores were significantly higher than pre-test scores for both groups, with t-values of -34.708 for the control group and -6.433 for the experimental group, both significant at the 0.000 level, well below the 0.05 threshold. These findings suggest that implementing storytelling in EFL classes can effectively improve students' speaking skills.Keywords: speaking skill, storytelling, improvement.DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202473